Modeling the nonaxisymmetric structure in the HD 163296 disk with planet-disk interaction - Rodenkirch, Peter; Rometsch, T.; Dullemond, Cornelis; Weber, P.; Kley, W. (Astronomy and astrophysics, 2021)
Context. High-resolution ALMA observations such as the DSHARP campaign have revealed a variety of rich substructures in numerous protoplanetary disks. These structures consist of rings, gaps, and asymmetric features. It has been debated whether planets can be accounted for among these substructures in the dust continuum. Characterizing the origin of asymmetries, as seen in HD 163296, might lead to a better understanding of planet formation and the underlying physical parameters of the system.Aims. We test the possibility that the formation of the crescent-shaped asymmetry in the HD 163296 disk can be attributed to planet-disk interaction. The goal is to obtain constraints on planet masses, eccentricities, and disk viscosities. Furthermore, we test the reproducibility of the two prominent rings in the HD 163296 disk at 67 and 100 au.Methods. We performed two-dimensional, multi-fluid, hydrodynamical simulations with the FARGO3D code, including three embedded planets in the setup. Dust is described via the pressureless fluid approach and distributed over eight size bins. The resulting grids were post-processed with the radiative transfer code RADMC-3D and CASA software to model the synthetic observations.Results. We find that the crescent-shaped asymmetry can be qualitatively modeled with a Jupiter mass planet at a radial distance of 48 au. Dust is trapped in the trailing Lagrange point L5, preferably, with a mass of between 10 and 15 earth masses. The observation of such a feature constrains the level of viscosity and planetary mass. Increased values of eccentricity of the innermost Jupiter mass planet negatively impacts the stability of the crescent-shaped feature and does not reproduce the observed radial proximity to the first prominent ring in the system. Generally, a low level of viscosity (α ≤ 2 × 10−3) is necessary to allow for the existence of such a feature. Including dust feedback in the leading point, L4, can dominantly capture dust for dust grains with an initial Stokes number ≤ 3.6 × 10−2. In the synthetic ALMA observation of the model with dust feedback, two crescent-shaped features are visible. The observational results suggest a negligible effect on the part of dust feedback since only one such feature has been detected so far. The dust-to-gas ratio may thus be overestimated in the models. Additionally, the planet mass growth time scale does not strongly affect the formation of such asymmetries in the co-orbital region.
Gesehen am 09.06.2021